2015
DOI: 10.3389/fnagi.2015.00005
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported physical activity and objective aerobic fitness: differential associations with gray matter density in healthy aging

Abstract: Aerobic fitness (AF) and self-reported physical activity (srPA) do not represent the same construct. However, many exercise and brain aging studies interchangeably use AF and srPA measures, which may be problematic with regards to how these metrics are associated with brain outcomes, such as morphology. If AF and PA measures captured the same phenomena, regional brain volumes associated with these measures should directly overlap. This study employed the general linear model to examine the differential associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…Lifestyle factors have a striking ability to empower the adult brain -strengthening plasticity, building cognitive reserve, and preventing functional decline. Physical activity in particular has emerged as a powerful life-style factor that can improve cognitive function Buchman et al, 2008;Erickson et al, 2010;Erickson et al, 2011;Kramer and Erickson, 2007a, b;Smith et al, 2010;Stubbs et al, 2017;Suwabe et al, 2018), reduce the risk of age-associated cognitive decline and AD (Buchman et al, 2012;Erickson et al, 2012;Hillman et al, 2008;Kirk-Sanchez and McGough, 2014;Korol et al, 2013;Prakash et al, 2015;Weuve et al, 2004;Yaffe et al, 2001), counteract age-and AD-related losses of grey and white matter (Baker et al, 2010;Best et al, 2017;Bherer et al, 2013;Erickson et al, 2014;Lautenschlager et al, 2008;Okonkwo et al, 2014;Suzuki et al, 2012;Voss et al, 2013;Zlatar et al, 2015) and counteract age-and AD-related declines in cognitive neural network function (Colcombe et al, 2004;Huang et al, 2016;Voss et al, 2010). While the benefits of physical activity are evident, the underlying mechanisms by which physical activity supports brain function and health and slows Aging-and AD-related declines in the human brain are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle factors have a striking ability to empower the adult brain -strengthening plasticity, building cognitive reserve, and preventing functional decline. Physical activity in particular has emerged as a powerful life-style factor that can improve cognitive function Buchman et al, 2008;Erickson et al, 2010;Erickson et al, 2011;Kramer and Erickson, 2007a, b;Smith et al, 2010;Stubbs et al, 2017;Suwabe et al, 2018), reduce the risk of age-associated cognitive decline and AD (Buchman et al, 2012;Erickson et al, 2012;Hillman et al, 2008;Kirk-Sanchez and McGough, 2014;Korol et al, 2013;Prakash et al, 2015;Weuve et al, 2004;Yaffe et al, 2001), counteract age-and AD-related losses of grey and white matter (Baker et al, 2010;Best et al, 2017;Bherer et al, 2013;Erickson et al, 2014;Lautenschlager et al, 2008;Okonkwo et al, 2014;Suzuki et al, 2012;Voss et al, 2013;Zlatar et al, 2015) and counteract age-and AD-related declines in cognitive neural network function (Colcombe et al, 2004;Huang et al, 2016;Voss et al, 2010). While the benefits of physical activity are evident, the underlying mechanisms by which physical activity supports brain function and health and slows Aging-and AD-related declines in the human brain are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic exercise has been increasingly associated with improvements in memory, executive function, and patterns of neural activity as assessed by fMRI [ 2 4 , 7 11 ]. Recent fMRI evidence has also indicated that increased levels of aerobic capacity in older adults are also associated with improvements in language function and a more efficient neural recruitment array during a semantic verbal fluency task.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a cross-sectional study, Zlatar et al, 2013, demonstrated that the neural recruitment array during a semantic verbal fluency task in physically active older adults resembled that of younger adults, while sedentary older adults showed decrements in suppression of areas that should be inhibited during the task. They went on to demonstrate that longer interhemispheric inhibition, as measured by transcranial stimulation, was associated with more negative task-related activity in the right and left posterior perisylvian cortex, suggesting that sedentary aging may result in losses in task facilitatory cortical motor inhibition [ 11 ]. As such, based on these findings, the losses of negative task-related activity may be mitigated by regular engagement in physical exercise [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of voxel-based morphometry (VBM) on structural MRI data has shown increased volume in overall brain mass as well as white and gray matter, specifically areas of the frontal cortex and hippocampus in physically active vs. sedentary older adults (Colcombe et al, 2003; Zlatar et al, 2015). Importantly, exercise interventions have also shown morphometric differences in these areas from pre-to post-exercise intervention (Colcombe et al, 2006; Erickson et al, 2011) with corresponding increases in cognitive function.…”
Section: The Influence Of Exercise On Neurobehavior and Plasticitymentioning
confidence: 99%